Sistem Informasi Kegiatan Kuliah Kerja Lapangan (KKL) di Sekolah Tinggi Teknologi Ronggolawe (STTR) Cepu Menggunakan Desain Unified Modeling Language (UML) - Muksan SAN Junaidi (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2022)
KKL is an academic activity that must be taken and taken by all Diploma and Bachelor students in groups or individually. At the STTR Cepu campus, the process of submitting KKL to the assessment is still done manually, so it takes quite a long time to search for student data, missing data and inconsistent KKL activity data. The purpose of this research is to design and develop an Information System for Online KKL Activities at the STTR Cepu campus. Using the waterfall model system development life cycle (SDLC) development method, design based on Unified Modeling Language (UML) and PHP programming language with MySQL database. The research data includes student MPA data for the last 3 years 2015-2018. The results of this study are the application of an KKL activity information system that helps make it easier for students in the process of registering activities, submitting activities and proposing guidance processes and reports on the results of KKL activities as well as being more time efficient and faster..